The Effect of Good Corporate Governance, Corporate Social Responsibility, Liquidity, and Leverage on Financial Performance through Earnings Management Mediation - Ilham Jiensa Wijaya; Fatchan Achyani; Banu Witono (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the effects of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), Liquidity, and Leverage on financial performance, with Earnings Management acting as a mediating variable. The research is based on data from publicly listed non-financial State-Owned Enterprises (SOEs) in Indonesia from 2020 to 2022. The hypotheses proposed include the direct effects of GCG, CSR, Liquidity, and Leverage on financial performance, as well as their influence through Earnings Management. Data were collected from annual financial reports available on the Indonesia Stock Exchange (IDX) website, and the analysis was conducted using the Partial Least Squares (PLS) method. The results show that Liquidity has a significant positive effect on financial performance, while GCG, CSR, and Leverage do not show significant direct or indirect effects. Earnings Management was found not to mediate the relationship between the variables and financial performance. These findings imply that while Liquidity plays a critical role in enhancing financial performance, the influence of GCG, CSR, and Leverage, as well as the role of Earnings Management, remains limited in the context of Indonesian SOEs. Future research could explore other mediating variables or focus on different industries or regions to further investigate these relationships.